Revisiting Molossus (Mammalia: Chiroptera: Molossidae) diversity: Exploring southern limits and revealing a novel species in Argentina - Chambi Velasquez, Micaela Ana (2024)
Understanding species diversity and delineating their boundaries are crucial for effective management and conservation efforts. In the case of bats, species identification holds particular importance from an epidemiological standpoint. The genus Molossus (Chiroptera: Molossidae) encompasses 15 species distributed across the Neotropics, ranging from the southeastern United States to Argentina. This genus exhibits two contrasting patterns of variation: some species are cryptic, while others are morphologically distinct yet genetically similar. This study explores the diversity of Molossus in Argentina through a molecular phylogenetic approach. We analyzed sequences from three molecular markers (cyt b, COI, and FGB) along with morphology data obtained from a sample of 64 individuals. Uni- and multivariate analyses of external and cranial measurements were conducted, alongside comparisons of external and cranial characteristics among species. Based on molecular and morphological differences, we describe a new species within the Molossus genus. This newly discovered species exhibits a broad distribution spanning the Paraná River basin across three distinct ecoregions. It is noteworthy that this species is pseudo-cryptic with respect to similar-sized species such as M. molossus and M. melini. Additionally, it is important to mention that all species in Argentina have overlapping distribution ranges. In summary, this study provides valuable insights into the diversity and distribution of Molossus bats in Argentina, employing molecular and morphological analyses. The discovery of a new species underscores the ongoing importance of comprehensive research efforts in understanding and conserving bat populations in the Neotropics.